Japan in a Dynamic Asia: Coping with the New Security Challenges - Sato, Yoichiro; Limaye, Satu (Lexington Books, 2006)
Japan in a Dynamic Asia examines a new phenomenon in Japanese foreign policy: Japan's increasing activism under the Koizumi administration. Behind this policy shift are the end of the Cold War, drastic growth of China, proliferation of weapons of mass destruction, and new transnational security threats. This book updates our understanding of Japan's rapidly changing foreign policies in the contexts of the new regional power balance and security concerns. Unlike most books on Japanese foreign policy, which focus mainly on U.S.-Japan relations, this book analyzes Japan's relations with individual Asian countries and sub-regions. The role of the United States - when relevant - is discussed in the contexts of these bilateral and multilateral relations. Editors Yoichiro Sato and Satu Limaye have gathered an impressive array of essays that will interest students of Japanese politics, foreign policy, and international relations in the Asia-Pacific region.